Intravenous Infiltration Resulting in Compartment Syndrome: A Systematic Review. Issue 2 (June 2018) - Pare, Joseph R.; Moore, Christopher L.
Abstract : Objective: To determine characteristics of patients who develop compartment syndrome (CS) from IV infiltration requiring surgical intervention. Methods: A systematic review was conducted of available English literature from 1990 to date. Key terms were entered into a MEDLINE search in addition to searching grey literature and references of included manuscripts. Inclusion criteria were cases of CS requiring surgical intervention from IV infiltration. Exclusions were cases associated with phenytoin because of the unclear mechanism leading to injury (purple glove syndrome). Cases were reviewed for demographics, clinical information, and outcomes. Results: Literature search resulted in 32 manuscripts meeting inclusion with 51 cases. Age ranged from 3 days to 81 years (19.6% age <1 year [10/51], 21.6% age 1–18 years [11/51], and 58.8% age >18 years [30/51]). IV sites were reported in 43 cases: hand 46.5%, forearm 46.5%, foot 4.7%, and leg 2.3% ([20/43], [20/43], [2/43], [1/43]). Of the 42 cases reporting patient mental status, 76.2% (32/42) had impaired mental state or limited communication including young age defined as younger than 3 years. Common associated agents were contrast 36.2%, IV fluid 34%, and mannitol 8.5% ([18/47], [16/47], [4/47]). One patient required hand amputation, 5 had persistent deficits, 36 had no long-term deficits, and 9 cases did not report patient outcomes. Conclusion: Compartment syndrome affects patients of all ages with a significant number of patients being pediatric and specifically younger than 1 year. Patients at highest risk of developing CS requiring surgery from IV infiltration are likely to have barriers to communication. Abstract : Supplemental digital content is available in the text.